Co-designing technical innovations in the context of agroecological living landscapes - Triomphe, Bernard; Ouattara, Songdah Désiré; Kumar, Gopal; Fuchs, Lisa E.; Sánchez Choy, José G.; Piraux, Marc; Mannai, Amal; Telma, Sibanda; Sib, Ollo; Smith, B.; Vall, Eric; Maliappan, Sudharsan; et al. (2024)
This report documents the processes, results, and key learnings from implementing co-design approaches for agroecological innovations across eight countries (Burkina Faso, India, Kenya, Laos, Peru, Senegal, Tunisia, and Zimbabwe) during 2023-2024, as part of Work Package 1 of the CGIAR Agroecology Initiative. The participating countries demonstrated significant diversity in their co-design approaches, reflecting different contexts, farming systems, and priorities. Several countries like Kenya and Zimbabwe implemented structured, multi-cycle processes with systematic stakeholder engagement, while others like Peru focused on specific value chains such as organic cacao production. The co-design process typically progressed through several key phases: preparatory work to establish foundations and relationships, stakeholder engagement and visioning to develop shared understanding and goals, collaborative technology identification and design, systematic trial establishment, robust monitoring and evaluation, knowledge exchange through field days and farmer-to-farmer learning, capacity building, and iterative refinement based on results and feedback. Stakeholder participation varied across countries but consistently involved farmers, international researchers, and extension services. Some countries achieved strong integration with national research organizations and private sector actors, though this remained a challenge in several locations. The process helped strengthen institutional collaboration and knowledge sharing between stakeholders while empowering farmers as active participants in innovation development. In Kenya, for example, the establishment of partnerships with farmer training centers as "host centers" created effective platforms for ongoing engagement and scaling. Across the initiative, countries tested approximately 30+ distinct technologies spanning various domains. These included innovations in soil health management, such as Zimbabwe's conservation agriculture practices and Tunisia's biochar applications; integrated pest management approaches like Kenya's plant-based biopesticides and Peru's organic disease management for cacao; water management technologies including India's solar irrigation systems; and crop-livestock integration methods demonstrated by Burkina Faso's dairy production innovations. The scale of implementation was significant, reaching 300-350 farmers (data from six countries only), though the intensity of engagement varied. Most countries implemented 1 or 2 experimental cycles during this period, with some achieving three cycles based on local growing seasons. Technology performance and adoption patterns showed strong context-dependency. Several technologies demonstrated significant potential for scaling, particularly where they aligned well with existing farming systems and provided clear economic benefits. Tunisia's forage intercropping systems showed marked improvements in soil health and animal nutrition, while Kenya's basic agroecological practices achieved widespread adoption through existing farmer networks. Burkina Faso's dairy management innovations demonstrated how integrated approaches could improve both productivity and resource efficiency. Several critical success factors for technology adoption were identified, including secure land tenure, access to adequate labor and resources, and strong institutional support systems. Common challenges included high initial investment costs, intensive labor requirements, and the need for technical knowledge and training. Gender dynamics played a significant role, with some technologies showing different adoption patterns between men and women farmers. Looking forward, the co-design experience generated valuable insights for future implementation. There is a clear need for standardized yet flexible methodological guidelines that maintain scientific rigor while allowing local adaptation. Future processes should better integrate activities across plot, farm, and landscape scales, while addressing multiple types of innovations including organizational and institutional ones. Enhanced mechanisms for inclusive participation, particularly of women farmers and diverse stakeholder groups, will be crucial for success. These results provide a strong foundation for refining and scaling these approaches through the upcoming Multifunctional Landscapes program. The experiences demonstrate that well-structured co-design approaches can generate both immediate benefits and longer-term transformative change in agricultural systems, particularly when supported by robust knowledge sharing platforms and communication systems. Success will require continued attention to both technical and social dimensions while maintaining flexibility to accommodate local contexts and emerging opportunities.